Problem-based learning in the teaching and learning of the Malaysian nationhood course at Universiti Utara Malaysia - Haniffa, Mohamed Ali; Rathakrishnan, Mohan; Omar, Salmah; Ismail, Nor Hanani (Global Academic Excellence, 2019)
This study discusses the implementation of Problem Based Learning (PBL) in teaching and learning Malaysian Nationhood course at Universiti Utara Malaysia (UUM). This course is a core course and should be taken as a prerequisite in the process of graduation. However, the significant challenge faced by instructors of the course is the course itself which is tedious and uninteresting. The number of students in classrooms and traditional teaching approach caused students to feel bored and uninterested. PBL is a Student Centered Learning (SCL) based model and it is able to produce a conducive learning environment. Aware of the constraints facing in delivering this course, PBL model is applied to increase students’ interests and enhance the level of students’ achievement for this course. This study is a simple descriptive analytical approach using information gathering through observation, SCL-focused activities and focus group discussion. The study found that the method of SCL is able to increase the interest and level of achievement of the students in the Malaysian Nationhood course at UUM.